Hydrolyzed collagen as a partial fat substitute in chicken burgers produced with white striping meat - Ana Clara L. Pavanello; Rebeca P.F. Catarino; Claudimara da S. Portela; Jaquellyne B.M.D. da Silva; Vinícius A.B. Mascareli; Viviane L.L. da Costa; Bárbara G. Vicenzi; Fernanda J. Mendonça; Sandra H. Prudencio; Tatiana C. Pimentel; Adriana L. Soares (Poultry Science)
White striping (WS) is an anomaly characterized by the appearance of white striations in the Pectoralis major muscles. This study aimed to evaluate the effect of animal fat replacement (chicken skin) with hydrolyzed collagen (HC, 0, 50 and 75%) on the characteristics of burgers with normal chicken breast fillets (FN) and WS. The samples were subjected to physical-chemical characterization, oxidative stability (TBARS), texture, and sensory profile. The utilization of WS meat increased the pH values, lipid content, and oxidation throughout storage, but it did not impair the sensory acceptance and sensory profile of the products. Adding HC reduced the pH in the formulations, changed the chemical composition (lower moisture and lipid content and higher protein and collagen content), and increased the texture parameters (hardness and chewiness). The formulations with 50% fat replacement showed similar sensory acceptance and purchase intention to the control products and were characterized by the typical texture and mild aroma and flavor. The results suggest that WS chicken meat and HC can be used to produce hamburgers with 50% replacement of animal fat without compromising the quality of the products.